1963
DOI: 10.1161/01.res.12.3.256
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between the Release and Tissue Depletion of Norepinephrine from the Heart by Guanethidine and Reserpine

Abstract: The release of norepinephrine from the heart of anesthetized open-chest dogs has been determined both after the intravenous administration of guanethidine (15 mg/kg) and after reserpine (3 mg/kg) by measuring the plasma norepinephrine concentration with the fluorometric method (THI) in bloods obtained simultaneously from the coronary sinus and femoral artery. In four dogs following the administration of guanethidine, norepinephrine release into the coronary sinus blood occurred and persisted for two to three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1964
1964
1988
1988

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…It was therefore concluded that reflex slowing resulting from vagal stimulation or withdrawal of sympathetic activity had been eliminated; rather, the direct chronotropic effect of norepinephrine was observed (11). Finally, after the conclusion of this series of experiments, the right atrium was biopsied in seven of the eight dogs whose hearts had been denervated, and the norepinephrine concentrations were determined by the trihydroxyindole photofluorometric method, as detailed elsewhere (12). No …”
Section: Methodsmentioning
confidence: 95%
“…It was therefore concluded that reflex slowing resulting from vagal stimulation or withdrawal of sympathetic activity had been eliminated; rather, the direct chronotropic effect of norepinephrine was observed (11). Finally, after the conclusion of this series of experiments, the right atrium was biopsied in seven of the eight dogs whose hearts had been denervated, and the norepinephrine concentrations were determined by the trihydroxyindole photofluorometric method, as detailed elsewhere (12). No …”
Section: Methodsmentioning
confidence: 95%
“…• The release of norepinephrine from the heart in response to direct stimulation of sympathetic nerves has been reported previously, but attempts to correlate the amount of endogenous neurotransmitter liberated with the intensity of physiological responses in vivo have been limited (1)(2)(3)(4)(5). For instance, an overflow of endogenous norepinephrine produced by a short period of stimulation has never been demonstrated at very low stimulation frequencies despite the fact that most innervated tissues respond physiologically to a frequency range of 1 to 3 Hz (6).…”
mentioning
confidence: 99%
“…Moreover, we observed that the effect of norepinephrine infusion on left ventricular dP/dt max did not differ after 60 min of left stellate ganglion stimulation (unpublished data). (Harrison et al 1963). These reduction rates are compatible with those seen in the present study.…”
Section: Discussionmentioning
confidence: 99%